Good living and economic solidarity in Villa del Carbón, Mexico: competing rationales - López Córdova, Dania (Cooperativismo & Desarrollo, 2016)
Purpose: This article seeks to present reflections on economic solidarity and good living based on findings in a small town near the country’s capital. Description: Villa del Carbón is a predominantly rural town, but, due to its location, it is a point of interconnection—a bridge between two important regions of the country—where the town brings together diverse times and spaces through a complexity that illustrates tensions between rationales. These rationales are, on the one hand, the processes of metropolization and development with their instrumental rationality and, on the other, the permanence and revision of ways oflife based on reproductive, solidarity, and liberating rationales. Viewpoint: It is argued that there are examples of economic solidarity such as forestry, apiculture, agroecological, and ecotourism productive organizations. However, these are constantly threatened and strained by the demands of development and capitalism. Conclusions: The features of economic solidarity practices—which make tangible alternative rationales, other rationales—should be considered to design and implement public policies of promotion and strengthening.
Keywords: agroecology; good living; development; rationales; reciprocity; economic solidarity